Genetic changes in the canonical Wnt/β-catenin signaling pathway in colorectal cancer - Aldecoa Bedoya, Franklin (2022)
The goal of this study is to better understand the complexity of the canonical Wnt/β-catenin (C-WNT) signaling pathway in colorectal cancer (CRC): how it works, its key mutations and the novel therapeutic compounds under development. PubMed, Scopus and SciELO were used to find the most relevant medical literature on the issue. The C-WNT signaling pathway regulates essential cellular biological processes: genetic changes in this pathway are significant contributors to CRC. The Wnt ligand binding to the Frizzled receptor and low-density lipoprotein receptor-related protein 5 or 6 (LRP5/6) stimulates the C-WNT signaling pathway; this extracellular membrane ternary complex activates kinases that promote phosphorylation of the intracellular domain of LRP5/6 and starts the cell signaling cascade. The C-WNT signaling pathway is changed in more than 90 % of all CRCs, with the adenomatous polyposis coli gene showing the great majority of mutations in this type of cancer. In recent years, the C-WNT signaling pathway has been an important target for researching new cancer treatments; various inhibitors of the pathway (monoclonal antibodies, inhibitory proteins, selective small compounds and other novel families) have been developed for the treatment of CRC, being the majority of them still in preclinical phases. In conclusion, CRC is related to mutations in the C-WNT signaling pathway, whose persistent activation provides cancer cells with self-renewing growth capabilities and is linked to treatment resistance in CRC. There is active research on novel and innovative compounds that affect this signaling pathway; however, none has received commercial approval so far.